Resilient, undercontrolled, and overcontrolled personality types based upon DSM-5 maladaptive personality traits - Gina Rossi; Laura C. Weekers; Joost Hutsebaut (Heliyon, 2021)
We explored the clinical relevance of resilient, overcontrolled and undercontrolled personality types based upon DSM-5 maladaptive personality traits. We examined if these prototypes could be differentiated in terms of personality functioning, and internalizing and externalizing pathology. Self-report questionnaires and structured interviews were administered to 192 adult patients referred to a mental health care center specialized in assessment and treatment of personality disorders. Through cluster analysis we identified a resilient type with no elevation on maladaptive trait domains and showing better personality functioning and less pathology than the overcontrolled and undercontrolled types. Furthermore, the overcontrolled type had elevated Negative Affectivity and a higher prevalence of mood disorders, whereas the undercontrolled type had elevations on all maladaptive traits, with the exception of Disinhibition, and higher rates of narcissistic and borderline personality disorders. Given the differences in psychopathology between the types, identifying these types may inform treatment focus. Also, in line with a stepped care model, compared to overcontrollers, resilient types may need less intensive treatment and undercontrollers may need more intensive treatment.